Peak-to-average power ratio reduction in wavelet packet modulation Using Binary Phase Sequence. - Vijaya M. Kulkarni; A. S. Bhalchandra (Institute of Advanced Engineering and Science, 2019)
A novel method of Peak–to-Average–Power-Ratio reduction is presented in this paper using WPT for multi carrier modulationand Riemann matrix for phase sequencing in SLM. Wavelet Packet Multicarrier Modulation(WPM) is a betteralternative to the existing multicarrier transmission system,OFDM system which suffers from high PAPR.Further reduction in Peak to Average Power Ratio (PAPR)is achieved by using Wavelet Packet Modulation(WPM) with SLM technique. Classical SLM uses random phases for phase rotations which suffers from the additional load of transmitting SI(side Information) to receiver. So to overcome a novel method is proposed here which uses the principle of varying the phases of the subcarrier data block to be transmitted ,using rows of the normalised Reimann matrix as phase sequence vectors for the Selected Mapping (SLM)Technique. The generated WPM frame with minimum PAPR is selected and transmitted .The proposed system achieves a significant improvement in PAPR reduction over the OFDM-classical SLM and WPM-classical SLM.